Herbivory as an important selective force in the evolution of floral traits and pollinator shifts - Jogesh, Tania (AoB Plants, 2016)
Floral trait evolution is frequently attributed to pollinator-mediated selection but herbivores can play a key role in shaping plant reproductive biology. Here we examine the role of florivores in driving floral trait evolution and pollinator shifts in a recently radiated clade of flowering plants, Oenothera sect. Calylophus. We compare florivory by a specialist, internal feeder, Mompha, on closely related hawkmoth- and bee-pollinated species and document variation in damage based on floral traits within sites, species and among species. Our results show that flowers with longer floral tubes and decreased floral flare have increased Mompha damage. Bee-pollinated flowers, which have substantially smaller floral tubes, experience on average 13% less Mompha florivory than do hawkmoth-pollinated flowers. The positive association between tube length and Mompha damage is evident even within sites of some species, suggesting that Mompha can drive trait differentiation at microevolutionary scales. Given that there are at least two independent shifts from hawkmoth to bee pollination in this clade, florivore-mediated selection on floral traits may have played an important role in facilitating morphological changes associated with transitions from hawkmoth to bee pollination.